2013
DOI: 10.1590/s1981-81222013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian Dark Earths: pathways to sustainable development in tropical rainforests?

Abstract: Fertile dark anthrosols associated with pre-Columbian settlement across the Amazon Basin have sparked wide interest for their potential contribution to sustainable use and management of tropical soils and ecosystems. In the Upper Xingu region of the southern Amazon, research on archaeological settlements and among contemporary descendant populations provides critical new data on the formation and use of anthrosols. These findings provide a basis for describing the variability of soil modifications that result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 52 publications
2
42
0
4
Order By: Relevance
“…The soil properties of terra preta locations are relatively homogeneous, which indicates active soil management. Ethnopedological research has shown that currently living Amerindian groups' lifestyle leads to the formation of black earth (Schmidt 2013). Even without this evidence, it would be plausible to presume that at least some of the indigenous groups formerly living in the Amazon consciously carried out soil management techniques by adding a combination of charcoal, ceramic sherds and organic material (human excrement).…”
Section: Research | Forschungmentioning
confidence: 99%
“…The soil properties of terra preta locations are relatively homogeneous, which indicates active soil management. Ethnopedological research has shown that currently living Amerindian groups' lifestyle leads to the formation of black earth (Schmidt 2013). Even without this evidence, it would be plausible to presume that at least some of the indigenous groups formerly living in the Amazon consciously carried out soil management techniques by adding a combination of charcoal, ceramic sherds and organic material (human excrement).…”
Section: Research | Forschungmentioning
confidence: 99%
“…Dark earths, or anthrosols, are rich soils believed to have been formed from the composting of human refuse. According to Denevan (:14), “soil improvement made permanent or semi‐permanent cultivation possible and thus larger populations than otherwise.” Schmidt () finds notable similarities between dark earth samples taken from contemporary Kuikuru villages and pre‐Columbian settlement remains in the Upper Xingú of southern Amazonia: Terra preta soils are primarily composed of refuse, including ceramics, and are found adjacent to dwelling sites, whereas lighter terra mulata soils show evidence of burning and other plant waste and are found on the edges of settlements.…”
Section: Indigenous Groups and Their Environmentsmentioning
confidence: 99%
“…With regard to Terras Pretas, a pattern of spatial organization of the settlements was identiied in diferent areas of Amazonia e.g. Upper Xingu region, Central Amazonia, Lower Trombetas River and Lower Tapajos River Schmidt 2013;Schmidt et al 2014). Even though this is a point of convergence where the formation of ADEs has a diversity of processes, it is related with both environmental and social/cultural factors.…”
Section: Implications For Understanding Ade Formationmentioning
confidence: 99%
“…Even though this is a point of convergence where the formation of ADEs has a diversity of processes, it is related with both environmental and social/cultural factors. It can therefore be diferent according to the function of the spaces within the archaeological site (Schmidt 2013;Schmidt and Heckenberguer 2009;Schmidt et al 2014).…”
Section: Implications For Understanding Ade Formationmentioning
confidence: 99%